PENGARUH PENGGUNAAN TEKNIK PEMODELAN TERHADAP KETERAMPILAN MENULIS BERITA - Sari, Resti Pramita; Thahar, Harris Effendi; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2016)
ABSTRACTÂ This research study aims to describe skills in writing news of students class VIII MTsN Kayu Kalek Kabupaten Pesisir Selatan without and with use modeling techniques, with describe the effect of the use of modeling techniques to writing news of students class VIII MTsN Kayu Kalek Kabupaten Pesisir Selatan. The type of this research is quantitative research done using experimental design. The results of the research are news writing skills student are in the control class qualification More than Enough (LdC),news writing skills students are in the experimental class qualification Good (B),and based on t-test result concluded that the alternative hypothesis (H1) is accepted as tcount> ttable (8,24>1,67).Â Kata kunci: pengaruh, teknik pemodelan, beritaÂ